2020
DOI: 10.1007/s10565-020-09532-6
|View full text |Cite
|
Sign up to set email alerts
|

MSC encapsulation in alginate microcapsules prolongs survival after intra-articular injection, a longitudinal in vivo cell and bead integrity tracking study

Abstract: Mesenchymal stem cells (MSC) are promising candidates for use as a biological therapeutic. Since locally injected MSC disappear within a few weeks, we hypothesize that efficacy of MSC can be enhanced by prolonging their presence. Previously, encapsulation in alginate was suggested as a suitable approach for this purpose. We found no differences between the two alginate types, alginate high in mannuronic acid (High M) and alginate high in guluronic acid (High G), regarding MSC viability, MSC immunomodulatory ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…In another study, using alginate as the encapsulating biomaterial, Khatab et al showed that after the intra-articular injection of MSCs into the knee joints of rats, the survival rates of encapsulated MSCs were significantly higher compared to non-encapsulated cells. Nonetheless, using a rat model of osteoarthritis, Khatab et al did not observe any significant difference between encapsulated and non-encapsulated MSCs in regard to their therapeutic effect, as the pain, the cartilage damage and the synovial inflammation remained unchanged between the studied groups [140]. In an another recent study, Chen et al utilized a mouse model of myocardial infarction and showed that transglutaminase cross-linked gelatin-encapsulated ADSCs were more successfully engrafted at the injury site, in comparison to non-encapsulated ADSCs, leading to improved cardioprotection [141].…”
Section: Improved Cell Viability and Proliferationmentioning
confidence: 93%
“…In another study, using alginate as the encapsulating biomaterial, Khatab et al showed that after the intra-articular injection of MSCs into the knee joints of rats, the survival rates of encapsulated MSCs were significantly higher compared to non-encapsulated cells. Nonetheless, using a rat model of osteoarthritis, Khatab et al did not observe any significant difference between encapsulated and non-encapsulated MSCs in regard to their therapeutic effect, as the pain, the cartilage damage and the synovial inflammation remained unchanged between the studied groups [140]. In an another recent study, Chen et al utilized a mouse model of myocardial infarction and showed that transglutaminase cross-linked gelatin-encapsulated ADSCs were more successfully engrafted at the injury site, in comparison to non-encapsulated ADSCs, leading to improved cardioprotection [141].…”
Section: Improved Cell Viability and Proliferationmentioning
confidence: 93%
“…Furthermore, it can also be used to deliver growth factors with adjustable release rates by changing the molecular weight ( Jiao et al, 2019 ). In order to enhance the chondrogenesis of MSCs in alginate, several studies have successfully delivered growth factor or genes to local MSCs, thus directs the fate of MSCs and increases sGAG and Col II production ( Davis et al, 2018 ; Khatab et al, 2020 ). As for GP cartilage regeneration, using an in vitro model of the GP chondrocytes seeded on alginate hydrogel scaffolds with exogenous factors also resulted in high viability, low level hypertrophy, and cartilage matrix deposition ( Coleman et al, 2007 ; Erickson et al, 2018 ).…”
Section: Cartilage Tissue Engineering For Gp Injuriesmentioning
confidence: 99%
“…In particular, it is extremely useful during cell therapy, wherein the membrane can create a barrier between the host cells and transplanted cells. MSCs could be entrapped within various biomaterials (e.g., hyaluronic acid, alginate, agarose, etc.,) that can also provide a physiologic environment that promotes cell survival [145], functionality [110], and prevent immune response [146] and cell fusion. Even though MSCs are immobilized within the microcapsules, they retain their paracrine functions, and manipulate their microenvironment, at the site of implantation, owing to the expression/overexpression of various therapeutic molecules.…”
Section: Challengesmentioning
confidence: 99%